Array detection enables large localization range for simple and robust MINFLUX - Eli Slenders; Sanket Patil; Marcus Oliver Held; Alessandro Zunino; Giuseppe Vicidomini (Light: Science & Applications)
Abstract The MINFLUX concept significantly improves the localization properties of single-molecule localization microscopy (SMLM) by overcoming the limit imposed by the fluorophore’s photon counts. Typical MINFLUX microscopes localize the target molecule by scanning a zero-intensity focus around the molecule in a circular trajectory, with smaller trajectory diameters yielding better localization uncertainties for a given number of photons. Since this approach requires the molecule to be within the scanned trajectory, MINFLUX typically relies on an iterative scheme with decreasing trajectory diameters. This iterative approach is prone to misplacements of the trajectory and increases the system’s complexity. In this work, we introduce ISM-FLUX, a novel implementation of MINFLUX using image-scanning microscopy (ISM) with a single-photon avalanche diode array detector. ISM-FLUX provides a precise MINFLUX localization within the trajectory while maintaining a conventional photon-limited uncertainty outside it. The robustness of ISM-FLUX localization results in a larger localization range and greatly simplifies the architecture, which may facilitate broader adoption of MINFLUX.